The application of the motivation-opportunity-ability model in predicting green entrepreneurial behavior of farmers - Zobeyde Kouchaky; Fatemeh Razzaghi Borkhani; Taher Azizi-Khalkheili; Fatemeh Ghorbani Piralidehi (Sustainable Futures)
The escalating environmental challenges linked to climate change, excessive resource consumption, biodiversity loss, and sustainability issues are largely human-driven, influenced significantly by the practices of business owners. Addressing these challenges necessitates behavioral shifts towards green entrepreneurship as a pathway to a sustainable future and environmental protection. This study models green entrepreneurial behavior (GEB) among greenhouse operators in Golestan Province, northern Iran, employing the Motivation-Opportunity-Ability (MOA) model, with a focus on socio-psychological structures. The research involved a complete survey of 70 vegetable greenhouse units in the region. Data analysis was conducted using structural equation modeling through the Partial Least Squares (PLS) method with Smart PLS3 software. Results revealed that the intention to adopt GEB had the strongest effect on behavior (path coefficient = 0.410, T-value = 4.369), followed by the ability and opportunity components. The latent variables of green entrepreneurial intention (GEI), opportunities, and abilities collectively explained approximately 75 % of the variance in GEB. Furthermore, the constructs of social norms, beliefs, and attitudes accounted for 76.4 % of the variance in GEI. These findings confirm the profound role of the MOA model in the adoption of green entrepreneurship and provide strategic recommendations for planners and policymakers to establish green entrepreneurship by improving the internal and external structure of the production system, emphasizing the complementary relationships between psychological, social, economic, and environmental factors in achieving sustainable development and food security.